Enabling next generation systems biology: a conversation with M. Madan Babu - Lemberger, Thomas (Mol Syst Biol, 2019)
Molecular Systems Biology warmly welcomes its new academic Chief Editor, M. Madan Babu. Madan shared his thoughts on the evolution of the field and the importance of bridging disciplines to enable next generation systems biology.